Hypothesis: Caco‐2 cell rotational 3D mechanogenomic turing patterns have clinical implications to colon crypts. Issue 12 (25th September 2018) - Zheng, Gen; Kalinin, Alexandr A.; Dinov, Ivo D.; Meixner, Walter; Zhu, Shengtao; Wiley, John W.
Abstract: Colon crypts are recognized as a mechanical and biochemical Turing patterning model. Colon epithelial Caco‐2 cell monolayer demonstrated 2D Turing patterns via force analysis of apical tight junction live cell imaging which illuminated actomyosin meshwork linking the actomyosin network of individual cells. Actomyosin forces act in a mechanobiological manner that alters cell/nucleus/tissue morphology. We observed the rotational motion of the nucleus in Caco‐2 cells that appears to be driven by actomyosin during the formation of a differentiated confluent epithelium. Single‐ to multi‐cell ring/torus‐shaped genomes were observed prior to complex fractal Turing patterns extending from a rotating torus centre in a spiral pattern consistent with a gene morphogen motif. These features may contribute to the well‐described differentiation from stem cells at the crypt base to the luminal colon epithelium along the crypt axis. This observation may be useful to study the role of mechanogenomic processes and the underlying molecular mechanisms as determinants of cellular and tissue architecture in space and time, which is the focal point of the 4D nucleome initiative. Mathematical and bioengineer modelling of gene circuits and cell shapes may provide a powerful algorithm that will contribute to future precision medicine relevant to a number of common medical disorders.